Family Economic Strategies through Digital Marketing: A Qualitative Study of Home-Based Businesses - Az Zahra, Puti; Purnomo, Purnomo; Saepudin, Asep; Shantini, Yanti; Rosmia, Ade Romi (Universitas Negeri Padang, 2025)
This study examines family economic strategies through digital marketing implementation in home-based businesses within community-based empowerment frameworks. Using a qualitative case study approach in Ibun District, Bandung Regency, West Java, this research involved 11 home-based business operators from the Local Hero women's community, selected through purposive sampling. Data collection employed triangulated methods including in-depth interviews, direct observation, and documentation analysis of digital marketing activities. Findings reveal that home-based businesses have evolved from supplementary income sources to primary economic pillars for family sustainability. Digital marketing strategies demonstrate sophisticated adaptation utilizing integrated platforms (WhatsApp Business, Facebook, and Shopee) with systematic approaches including visual content optimization, strategic promotional timing, and sustained customer engagement of 2-4 interactions weekly. Family involvement transcends labor distribution, creating collaborative entrepreneurial ecosystems that reinforce social cohesion and intergenerational knowledge transfer. The Local Hero community functions as a critical enabler, providing structured learning frameworks, peer experience sharing, and digital marketing networks that strengthen family economic positioning. This research contributes to theoretical understanding of community-mediated digital transformation in family economies and offers practical frameworks for scaling technology-based economic empowerment initiatives in similar socio-economic contexts. Keywords: Digital Economy, Community Empowerment, Home-Based Enterprises, Family Economic Strategy, Digital Marketing